Predictions and visualization for confirmed, recovered and deaths COVID-19 cases in Iraq - Wisam Dawood Abdullah; Abdulrahman Ahmed Jasim; Layth Rafea Hazim (Institute of Advanced Engineering and Science, 2022)
The 2019-2020 coronavirus pandemic is an emerging infectious disease that has been referred to as the